IJCM_367A: Mapping the Terrain of Learning: A Study on the Association between Self- Directed Learning Readiness and Learning Environment Dynamics among Students studying in a Public Health Institute in Kolkata - Ghosh Soumik; Paul Bobby; Bandyopadhyay Lina; Sahu Monalisha; Bhattacharyya Madhumita; Basu Rivu (Wolters Kluwer Medknow Publications, 2024)
Background: Self-directed learning (SDL) is the process in which individuals take the initiative and learning environment involves all other aspects of the institute. Good SDL ability is the foundation of lifelong learning. Students' perception of the educational environment plays a subtle role in learning and contributes to learning input and students' achievement. Self- directed learning is integral to public health teaching Objectives: To assess the perceptions of learning environment and self- directed learning readiness and the association between the two among public health students Methodology: A cross-sectional study was conducted from July to December 2023 in a public health institute in Kolkata. A total of 102 participants across five courses were selected by Census method and their self-directed learning readiness (SDLRS) and perceptions of learning environment were assessed using a self-administered questionnaire. The collected data was analysed using descriptive and inferential statistics in SPSS, version 16. Ethical approval was taken from Institutional Ethics Committee of AIIH&PH, Kolkata. Results: The mean age of the study participants was 26.7 years and 64.7% of the study participants were from MBBS background. The median academic hours was 18 hours per week and around 37.3% of the participants were studying in the institute for less than 6 months and 20.6% for more than 24 months. There was significant positive correlation between SDLRS and Learning Environment (Spearman's rho=0.281, p=0.004). SDLRS and perceptions of Learning environment improved with increase in duration of studying. Age(p=0.015) and prior academic qualification(p=0.016) were significantly associated with SDLRS. Conclusion: SDLRS is associated with positive Learning Environment. SDL ability can be improved by changing the learning environment to include new student-centered teaching methods. The duration of studying in the institute is also an important driver to inculcate self directed learning ability among the participants.